Biodiversity conservation in private forests: Factors driving landowner's attitude. (February 2022) - Baranovskis, Ģirts; Nikodemus, Oļģerts; Brūmelis, Guntis; Elferts, Didzis
Abstract: In many countries, biodiversity conservation strategies are aimed not only for state land, but also private land. Participation of landowners in conservation programmes can be viewed as a continuum from voluntary by the landowner to force by the existing legislation. The biodiversity conservation system of Latvia represents a case where in certain situations (such as establishment of micro-reserves) strict forest management restrictions can be implemented without acceptance of landowners. This causes conflicts with forest owners, which can negatively affect the success of reaching biodiversity conservation goals. Therefore, we aimed to explore factors driving private forest owner's attitude towards biodiversity conservation in their land. Mixed-mode survey was utilized for gathering information from 386 private forest owners. Ordinal logistic regression (OLS) models were used to analyze relationships between predictor and response variables. Our results suggested that financial dependence on income from forest harvest was the main factor causing negative attitude of landowners towards biodiversity conservation measures for private land of Latvia. This factor was significantly correlated with a forestry background (education, occupation and size of forest land). However, landowner education and general conservation values also influenced landowner willingness to accept conservation measures on private forest land. We highlighted a great potential for voluntary biodiversity conservation mechanisms in Latvia, which could complement existing (regulatory approach based) biodiversity conservation instruments.